Organizational Culture Moderates The Mediating Effect Of Motivation On The Influence Of Discipline And Incentives Toward Employees Performance - Lumbantobing, Rudolf (2019)
This research explores the moderating effect of organizational culture on the mediating effect of motivation on the influence of discipline and incentives toward employees' performance. This study involved Indonesia media employee respondents. The developed hypotheses were analyzed using moderates regression analysis and path analysis. The findings showed that motivation played a significantly positive effect to mediate the effect of discipline and incentives toward employees' performance. Further, showed that employee performance was significant negatively influenced by the interaction effect between incentives and motivation with organizational culture. These findings conclude that the positive effects of incentives on employees' performance might be more positive when motivation and organizational culture interacted on the contrary level. The findings of this study suggested that when the organizational culture was held by among organizational members as high as employees’motivation that implies increasing discipline and incentives could increase employees' performance would be better.